Mn\(_{55-x}\)Co\(_x\)Bi\(_{45}\) Melt Spun Ribbons: Microstructures and Magnetic Properties - Nguyen, Truong Xuan; Vuong, Anh Kha; Dang, Ngan Thuy Thi; Nguyen, Nam Hoai; Pham, Nam Hong; Quynh, Nguyen Van; Tuan, Dinh Van; Nguyen, Vuong Van (Communications in Physics, 2022)
In this paper, we present the effect of Cobalt (Co) addition on the crystallization, microstructures and magnetic properties of Mn55-xCoxBi45 (x = 0, 5, 10, 20) melt – spun ribbons. The ribbons were prepared by the melt-spinning techique and subsequent anneal at 280 oC for 5 h. The investigations by using X-ray diffraction (XRD), Differential Scanning Calorimetry (DSC) traces as well the Vibration Sample Magnetometer (VSM) measurements result in the optimal content of Co added to the MnBi system is arounf 5 %at. The larger Co content causes the eutectic Mn-Co formation which restricts the reaction between Mn and Bi to form MnBi ferromagnetic phase responsible for ribbons’ performance the saturation magnetization Ms. The maximum saturation magnetization Ms of 65emu/g and the coercivity iHc of 4.7 kOe was achived for the ribbon of Mn50Co5Bi45. The effect of Co content on the microstructures and magnetic properties of Mn55-xCoxBi45 melt – spun ribbons will be discussed in detail.